EFEK MONITORING MECHANISM TERHADAP KINERJA KEUANGAN DAN KINERJA PASAR - Agus Setiawaty (FORUM EKONOMI, 2015)
The main objective of this research is to analyse impact of monitoring mechanism of corporate governance to comprehensive corporate performance, both financial performance and market performance. This research was conducted using secondary data obtained from annual reports of manufacture companies listed in the Indonesia Stock Exchange for the year 2011 until 2013. The data was analyzed using multiple regression method to capture the effect of corporate governance mechanism to company performance. Â The result showed that institutional shareholding and leverage partially and significantly affect financial performance, whilst board size, commissioner size, independent commissioner, managerial shareholding, audit committee size are found to insignificantly affect financial performance. Furthermore, board size, commissioner size and institutional shareholding significantly affect market performance whereas independent commissioner, managerial shareholding, audit committee and leverage do not influence market performance.Â Key Word: board size, commissioner size, institutional shareholding and market performance